A pas de deux for a cathedral and a hunchback: Roland Petit’s ballet Notre-Dame De Paris - Buhrle, IJ (Oxford University Press, 2019)
In 1965, the French choreographer Roland Petit set himself the task of making a ballet out of Victor Hugo’s voluminous novel Notre-Dame de Paris. The result departed radically from earlier attempts to transpose the work into movement by choreographers who included Jules Perrot and Marius Petipa. Although the love plot (which revolves around a dancer), the wide range of emotions depicted, the stark contrasts, and alternation between crowd scenes and more intimate scenes favour its transposition into a ballet, the novel also presents numerous difficulties, such as the importance of politics, philosophy and architecture. Quasimodo, Frollo and the cathedral seem rather unsuitable protagonists for a ballet. This paper argues that Petit’s adaptation of Notre-Dame de Paris engaged with the literary source on a much deeper level than its predecessors. Petit’s innovative ballet does not merely illustrate the novel: it reveals underlying elements in the source and sheds new light on it.